Implementasi Model Auditory Intellectually Repetition (AIR) Dengan Media Geoboard Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Kelas IV B - Nurul Izzah Ramadhani Al-Syawat; Mukhlis Mukhlis; Hamdana Hadaming (Journal on Education, 2024)
This study aims to improve the mathematical problem-solving skills of Grade IV B students at UPT SPF SD Negeri Balang Baru 1 through the implementation of the Auditory Intellectually Repetition (AIR) model with the assistance of Geoboard media. The method used was Classroom Action Research, involving all Grade IV B students, consisting of 13 male and 13 female students. Data were collected through tests and observations, with quantitative analysis used to measure problem-solving abilities and qualitative analysis used to evaluate teacher and student activities. The results showed that the average mathematical problem-solving skills of the students increased to 76.25%. Teacher activity improved from 94.5% in Cycle I to 96.7% in Cycle II, while student activity increased from 93.28% to 97.42%. These findings indicate that the implementation of the AIR model with Geoboard media is effective in enhancing students' mathematical problem-solving skills